Ninth Five Year Plan 1997-2002 Volume-IV Government of Assam - Planning Commission (Planning Commission, 1997)
As such, it is seen that there is a backlog of 909.571 Km, 680.959 Km. and 22977.938 Km. for Kms, MDRs and ODRs respectively to be achieved by 2001 A.D. Out of 25253.532 Km. of roads, only 4641.692 Km. of roads are surfaced so far. The percentage of surfaced roads is 18.38% against the National Average of about 40%, which indicates huge backlog so far surfaced roads are concerned. Further, in respect of road length, the achievement, so far, is only about 40 Km. per 100 Sq.Km. of territorial area against the target of 82 Km, per 100 Sq.Km. as per development plan 1981-2001 for Assam. Calculated backlog in respect of ODR/VR on the plains Districts of Assam is to the extent of 2300 km,, which will require staggering amount of Rs. 3500.00 Crores as per the approved Master plan which should be completed within 2001 A.D.
Planning and Development Department Government of Assam